The Initial Teaching Alphabet (i.t.a.). Specialised Bibliography B2 - British Council, London (England). English-Teaching Information Centre; British Council, London (England). English-Teaching Information Centre ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1975)
This bibliography cites periodicals, books, sections of books, and articles having to do with the initial teaching alphabet. Entries include American and European publications, most published since 1965. (CLK)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Alphabets; Bibliographies; English (Second Language); Initial Teaching Alphabet; Language Instruction; Reading Instruction; Reference Materials; Resource Materials; Second Language Learning; Written Language; Reference Materials, Bibliographies